Efektivitas Senam Lansia dan Senam Ergonomis Terhadap Perubahan Skala Insomia pada Lansia - Susisusanti; Fani, Rif'atul (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Insomnia in the elderly is a health problem that impacts quality of life and cognitive function. Non-pharmacological interventions such as physical activity are effective alternatives in improving sleep quality. This study aims to analyze the effectiveness of elderly exercise and ergonomic exercise on changes in the insomnia scale in the elderly and to compare the effectiveness of the two interventions. This study used a quasi-experimental design with a two-group pretest-posttest. The sample consisted of 40 elderly people divided into two groups, each with 20 respondents. The intervention was carried out for four weeks with a frequency of three times per week. Measurements used the Insomnia Severity Index (ISI). Data analysis was performed using paired sample t-tests and independent t-tests. The results showed a significant decrease in insomnia scores in the elderly exercise group (p=0.001) and ergonomic exercise group (p=0.000). In addition, the results of the independent t-test showed a significant difference in effectiveness between the two groups (p=0.023), where ergonomic exercise was more effective than elderly exercise in reducing insomnia scores. The conclusion of this study indicates that both interventions are effective in reducing insomnia in older adults, but ergonomic exercise provides more optimal results. These findings can inform the development of community-based nursing interventions to improve sleep quality in older adults